PENERAPAN STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN SIKAP SISWA TERHADAP FISIKA DI KELAS XI IPA SMA MUHAMMADIYAH BANGKINANG - Reza Despita Amelia; Zulhelmi '; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract This reasearch aimed to determine students' attitudes on physics between after and before the implementation of active learning strategy of verbal soccer on kinetic gas theory material. The subject of this research is the students of grade XI IPA SMA Muhuammadiyah Bangkinang, which consists of 30 students. Data in this research is primary data obtained from prestest and posttest score of students using questionnaire attitude of student to physics then analyzed descriptively. The attitude post on physics consists of four indicators of interest in physics, physics learning, the importance of physics and the views of the physical environment. Based on the data analysis, the students 'attitudinal score on the physics of the beginning and the end with the high category was analyzed by using the gain where the students' attitude toward physics was obtained by 0.19 with the low category. Thus it can be concluded that the active learning strategy of verbal football can improve students' attitudes toward physics with low categoryKey Words: Attitudes to Physics, Verbal Soccer, Gas Kinetic Theory